The Role of ChatGPT in Enhancing Paraphrasing Skills to Minimize Plagiarism in Student Assignments - Triana, May Devi; Naibaho, Sriwi Anceli; Sihite, Sepania Handayani Br; Hartati, Rita (CV. Rayyan Dwi Bharata, 2025)
The innovation of artificial intelligence (AI) in education has opened up new avenues to improve academic skills, especially in improving paraphrasing and reducing plagiarism. This research explores the role of ChatGPT, an AI-based language model developed by OpenAI, in helping university students improve paraphrasing and avoid plagiarism in academic tasks. Using quantitative methods, a survey was conducted among 30 university students to assess their experiences and perceptions of ChatGPT's effectiveness. The results showed that 76.7% of students reported improvement in paraphrasing skills after using ChatGPT, and 46.6% believed that ChatGPT helped reduce plagiarism. However, some respondents remained neutral or sceptical about the effectiveness of this tool. Although the findings suggest that ChatGPT can be a valuable resource in academic writing, this study highlights the need for further refinement of this technology and more comprehensive guidelines for its use. This research provides insights for students and educators in integrating AI tools such as ChatGPT to foster academic integrity and improve reding skills.